Internal Factor Evaluation (Ife) and External Factor Evaluation (EFE) Methods in Educational Strategy Planning - Ahmad Fauzan Syakir; Moh Dannur; Lisnawati Lisnawati (LP2M IAI AL-KHAIRAT PAMEKASSAN, 2025)
The growing number of private Islamic educational institutions in Indonesia has intensified competition in educational management, yet most institutions still lack structured tools for strategic environmental analysis. This study aims to examine the conceptual application of the Internal Factor Evaluation (IFE) and External Factor Evaluation (EFE) matrix methods in strategic planning for Islamic educational institutions, particularly in identifying internal strengths and weaknesses as well as external opportunities and threats. This study employed a systematic literature review (SLR) methodology, drawing on 30 peer-reviewed sources published between 2013 and 2026, retrieved from Google Scholar, Scopus, DOAJ, and the Indonesian national journal index (Sinta). Data were analyzed through three stages: literature reduction, content analysis, and integrative thematic synthesis. The findings reveal that the IFE and EFE matrices offer a quantitative and structured approach to environmental scanning that surpasses conventional SWOT analysis in terms of precision and accountability. When contextualized for Islamic educational settings, these tools can accommodate institution-specific internal factors such as Islamic values, pesantren culture, and character education commitments alongside conventional managerial variables. The study concludes that systematic application of IFE and EFE matrices enables Islamic school leaders to formulate data-driven strategies, optimize limited resources, and enhance institutional competitiveness. This study contributes a contextual conceptual framework that bridges strategic management theory and the practical realities of Islamic private school governance in Indonesia.